2020
DOI: 10.1002/cmdc.202000179
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Synthesis of Novel Cylindrocyclophanes that Inhibit Methicillin‐Resistant Staphylococcus aureus (MRSA)

Abstract: The cylindrocyclophanes are a family of macrocyclic natural products reported to exhibit antibacterial activity. Little is known about the structural basis of this activity due to the challenges associated with their synthesis or isolation. We hypothesised that structural modification of the cylindrocyclophane scaffold could streamline their synthesis without significant loss of activity. Herein, we report a divergent synthesis of the cylindrocyclophane core enabling access to symmetrical macrocycles by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The Hoye group and the Nicolaou group used Horner–Wadsworth–Emmons olefination and Ramberg–Bäcklund olefination to establish macrocyclic scaffolds, respectively [6] . Despite these advances, the chemical synthesis of other [7.7]paracyclophane natural products has not been reported, and structure–activity relationship (SAR) studies of these compounds are very limited [7] . Therefore, it is highly desirable to develop a concise and efficient synthetic route that can facilitate the structural diversification of [7.7]paracyclophane natural products and SAR studies.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The Hoye group and the Nicolaou group used Horner–Wadsworth–Emmons olefination and Ramberg–Bäcklund olefination to establish macrocyclic scaffolds, respectively [6] . Despite these advances, the chemical synthesis of other [7.7]paracyclophane natural products has not been reported, and structure–activity relationship (SAR) studies of these compounds are very limited [7] . Therefore, it is highly desirable to develop a concise and efficient synthetic route that can facilitate the structural diversification of [7.7]paracyclophane natural products and SAR studies.…”
Section: Figurementioning
confidence: 99%
“…To this end, our target molecules, including cylindrocyclophanes A and F and merocyclophanes A and D, are disconnected at C(7-8) and C(20-21) to afford monomeric compounds 5 a-d (Scheme 1). In contrast to the alkene metathesis and olefination approaches, the enzymatic Friedel-Crafts alkylation established the stereochemistry of C (7) and C(20) while forging the C(7-8) and C(20-21) connections. Previously, Balskus and co-workers demonstrated that CylK could catalyze the intermolecular Friedel-Crafts alkylation of several alkyl halides and resorcinols.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The ring-opening C–C activation/cross-coupling of cyclopropyl ketones results in valuable γ-substituted silyl enol ethers that can be challenging to access by other approaches (Scheme ). The most-developed approach to these products is conjugate addition under conditions to trap the enolate as the silyl enol ether, but this can be challenging for certain substitution patterns and functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The ring-opening C-C activation/cross-coupling of cyclopropyl ketones results in valuable γ-substituted silyl enol ethers [29][30][31][32][33][34][35] that can be challenging to access by other approaches (Scheme 2). The mostdeveloped approach to these products is conjugate addition under conditions to trap the enolate as the silyl enol ether, but this can be challenging for certain substitution patterns and functional groups.…”
Section: Introductionmentioning
confidence: 99%